Role of Macroscopic Image Enhancement in Diagnosis of Non-Muscle-Invasive Bladder Cancer: An Analytical Review - Mulawkar, Prashant Motiram; Sharma, Gyanendra; Tamhankar, Ashwin; Shah, Utsav; Raheem, Rickaz (Frontiers in Surgery, 2022)
Early diagnosis of non muscle invasive bladder cancer (NMIBC) is of paramount importance to prevent the morbidity and mortality due to bladder cancer. Though white light imaging (WLI) cystoscopy has long been considered the gold standard to diagnose bladder cancer, it can miss the lesion in a substantial percentage of patients. To improve the diagnostic efficacy of cystoscopy various optical image enhancement modalities have been studied. Photodynamic diagnosis (PDD), narrow band imaging (NBI) and Storz image 1 S enhancement are the macroscopic image enhancements. A relevant search was done for literature describing the macroscopic image enhancement modalities. PDD has been shown to be more sensitive over WLI in detection of bladder cancer. It is superior to WLI in detection of flat lesions. Bladder tumour resection (TURBT) with PDD yields more complete resection and reduced recurrence rates. PDD guided TURBT may have some role in reducing the risk of progression. NBI provides increased contrast between normal and abnormal tissues based on neo-vascularization thereby augmenting WLI. NBI requires a special light source. NBI is superior to WLI in detection of bladder cancer. Addition of NBI to WLI improves detection of flat lesions like carcinoma in situ. NBI is not useful in predicting invasive tumour or grade of tumour. NBI directed TURBT reduces recurrence rates and recurrence free survival. But its efficacy in retarding progression is unproven. Image 1 S-enhancement utilizes software-based image enhancement modes without need of special light source or intravesical contrast instillation. Another advantage of this system is simultaneous side-by-side visualization of WLI and enhanced image providing WLI image as control for comparison. As with PDD, S-enhancement produces lower rate of missed bladder cancer diagnosis. The sensitivity and negative predictive value of the image 1 S enhancement increases with increasing cancer grade. Negative test by S-enhancement effectively rules out NMIBC. All the image enhancement modalities have proven their utility in improved detection and short-term cancer control. But none of these modalities has proven its utility in delaying progression or long-term cancer control. Last word in this regard is yet to be written.